Research advances in the study of sleep disorders, circadian rhythm disturbances and Alzheimer’s disease - Xiong, Xiangyang; Hu, Tianpeng; Yin, Zhenyu; Zhang, Yaodan; Chen, Fanglian; Lei, Ping (Frontiers in Aging Neuroscience, 2022)
Although there are still no satisfactory answers to the question of why we need to sleep, a better understanding of its function will help to improve societal attitudes toward sleep. Sleep disorders are very common in neurodegenerative diseases and are a key factor in the quality of life of patients and their families. Alzheimer's disease (AD) is an insidious and irreversible neurodegenerative disease. Along with progressive cognitive impairment, sleep disorders and disturbances in circadian rhythms play a key role in the progression of AD. Sleep and circadian rhythm disturbances are more common in patients with AD than in the general population and can appear early in the course of the disease. Therefore, this review discusses the bidirectional relationships among circadian rhythm disturbances, sleep disorders, and AD. In addition, pharmacological and nonpharmacological treatment options for patients with AD and sleep disorders are outlined.